Методи підвищення надійності й інформаційної безпеки системи віддаленого доступу до телекомунікаційного обладнання - Воробйов, Іван; Великодний, Дмитро; Vorobiov, Ivan; Velykodnyi, Dmytro (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто комплекс методів підвищення надійності й інформаційної безпеки (ІБ) системи віддаленого доступу до телекомунікаційного обладнання для навчальних лабораторій. Сформовано модель загроз багатокористувацького середовища та визначено критичні вразливості доступності, ізоляції й керування доступом. Запропоновано резервування ключових сервісів і мережевих шляхів, балансування навантаження та self-healing контейнерних компонентів із централізованим моніторингом і журналюванням. Для зниження ризиків несанкціонованого доступу обґрунтовано використання TLS‑шифрування, RBAC/MFA й сегментації мережі. Ефективність підходу підтверджено порівняльною оцінкою базової й удосконаленої системи за показниками часу відновлення, ізоляції користувачів і керованості інфраструктури. /// EN: The paper substantiates a set of methods aimed at improving the reliability and information security of a remote access system to telecommunication equipment used in educational laboratories. Such platforms combine server components, network infrastructure and real devices, therefore failures of critical services or incorrect user actions may disrupt laboratory sessions, while insufficient isolation and weak access control create risks of unauthorized interference. A threat model for a multi-user environment is outlined and the most significant vulnerability groups are identified, including authentication and authorization weaknesses, network-level attacks, insufficient isolation of user sessions, availability threats, and insider misuse. To ensure fault tolerance, the approach integrates redundancy of key services and network paths, load balancing (L4/L7) and automated recovery of containerized components through health checks and self-healing policies. Centralized monitoring and logging are used to detect failures and anomalies, while configuration backup and rapid rollback mechanisms support the continuity of laboratory operation. To strengthen security, encrypted communication channels (TLS/SSH), role-based access control with multi-factor authentication, network segmentation and auditing of user actions are applied. The proposed integration aligns architectural decisions, protection mechanisms and administration procedures into a single workflow that supports stable operation under peak loads and improves manageability. A comparative evaluation of the baseline and improved systems indicates a reduction of recovery time after failures, higher user isolation level, and improved resistance to common network attacks, confirming the practical applicability of the proposed methods in remote telecommunication laboratories.
Methods for improving reliability and information security of a remote access system to telecommunication equipment
Keywords: віддалений доступ; телекомунікаційне обладнання; надійність; інформаційна безпека; контейнеризація; RBAC; MFA; TLS; сегментація мережі; журналювання; remote access; telecommunication equipment; reliability; information security; containerization; load balancing; redundancy; network segmentation